Evaluating the significance of radical reformation exemplified by Lutheran spiritualists and the Anabaptists to global christianity (2021)
The efforts of the fourteen century revivalist movements served as eye-openers to the rots in the Church. All of them leveraged on Biblical information as strategy to sanitize the Church that was invaded by worldliness and guided largely by traditions, human pronouncements as well as some unscriptural practices. With the sixteen century decisive reformation masterminded by Martin Luther, people had thought that the efforts of the reformers were the last move that Christianity needed to sanitize the Church but the rise of radical reformers suggested that over-emphasis of some doctrinal issues at the expense of others of great importance by the classical reformers deprived the Church of reconstruction it needed. This paper attempts to examine the roles played by some individuals and groups to radicalize Christianity through their brand of reformation; and consequently bring to the fore the implications of their expressed concerns on the Church, using historical method.